Burden of cardiovascular disease across 29 countries and GPs' decision to treat hypertension in oldest-old - Sven Streit; Jacobijn Gussekloo; Robert A. Burman; Claire Collins; Biljana Gerasimovska Kitanovska; Sandra Gintere; Raquel Gómez Bravo; Kathryn Hoffmann; Claudia Iftode; Kasper L. Johansen; Ngaire Kerse; Tuomas H. Koskela; et al. (Taylor & Francis Group, 2018)
Objectives: We previously found large variations in general practitioner (GP) hypertension treatment probability in oldest-old (>80 years) between countries. We wanted to explore whether differences in country-specific cardiovascular disease (CVD) burden and life expectancy could explain the differences. Design: This is a survey study using case-vignettes of oldest-old patients with different comorbidities and blood pressure levels. An ecological multilevel model analysis was performed. Setting: GP respondents from European General Practice Research Network (EGPRN) countries, Brazil and New Zeeland. Subjects: This study included 2543 GPs from 29 countries. Main outcome measures: GP treatment probability to start or not start antihypertensive treatment based on responses to case-vignettes; either low (<50% started treatment) or high (≥50% started treatment). CVD burden is defined as ratio of disability-adjusted life years (DALYs) lost due to ischemic heart disease and/or stroke and total DALYs lost per country; life expectancy at age 60 and prevalence of oldest-old per country. Results: Of 1947 GPs (76%) responding to all vignettes, 787 (40%) scored high treatment probability and 1160 (60%) scored low. GPs in high CVD burden countries had higher odds of treatment probability (OR 3.70; 95% confidence interval (CI) 3.00-4.57); in countries with low life expectancy at 60, CVD was associated with high treatment probability (OR 2.18, 95% CI 1.12-4.25); but not in countries with high life expectancy (OR 1.06, 95% CI 0.56-1.98). Conclusions: GPs' choice to treat/not treat hypertension in oldest-old was explained by differences in country-specific health characteristics. GPs in countries with high CVD burden and low life expectancy at age 60 were most likely to treat hypertension in oldest-old.Key Points  • General practitioners (GPs) are in a clinical dilemma when deciding whether (or not) to treat hypertension in the oldest-old (>80 years of age).  • In this study including 1947 GPs from 29 countries, we found that a high country-specific cardiovascular disease (CVD) burden (i.e. myocardial infarction and/or stroke) was associated with a higher GP treatment probability in patients aged >80 years.  • However, the association was modified by country-specific life expectancy at age 60. While there was a positive association for GPs in countries with a low life expectancy at age 60, there was no association in countries with a high life expectancy at age 60.  • These findings help explaining some of the large variation seen in the decision as to whether or not to treat hypertension in the oldest-old.